Community Empowerment of the Pokdarwis Group through Training on the Utilization of Water Hyacinth as EGO-PURL Compost - Nur Ani; Djatmiko Hidajat; Wartini (Universitas Veteran Bangun Nusantara, 2025)
ABSTRACT Introduction : Ngargorejo Village, Ngemplak District, Boyolali Regency, the place where the Cengklik Reservoir is located. These reservoirs are the main source of livelihood (fishermen, karamba farmers, tour boat captains, and traders). Based on the SWOT analysis, the condition of Pokdarwis partners has environmental issues related to the very rapid growth of water hyacinths that disrupt the natural ecosystem. The work program appointed is EGO-PURL (Environmental Friendly Fertilizer Water Hyacinth) Fertilizer Manufacturing Training. Objective : Increase the empowerment and knowledge of water hyacinth utilization training participants into, EGO-PURL Compost. Method: This activity involved the Target Partner of Pokdarwis